1964
DOI: 10.1172/jci105029
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Reticuloendothelial System (RES). III. Blockade of the RES in Man *

Abstract: In a previous communication (1), we have presented data indicating that the phagocytic capacity of the reticuloendotheial system (RES) in man can be determined safely and effectively by measuring the rate of disappearance of various doses of radioisotopically labeled aggregated human serum albumin particles from the blood after intravenous injection. Subsequently we reported that in patients with pneumococcal pneumonia, typhoid fever, and pneumonic tularemia (2), the phagocytic capacity of the RES was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…It has also been reported that the same strategy worked for iron oxide nanoparticles 23 or carbon 29, evidenced by qualitative or semi-quantitative comparison. Meanwhile, several authors reported that they did not observe RES depression following a primary dose of colloid during a secondary dose of different colloid 38. They attributed this to the fact that opsonization of the first material did not necessarily cause RES depression of the second material.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that the same strategy worked for iron oxide nanoparticles 23 or carbon 29, evidenced by qualitative or semi-quantitative comparison. Meanwhile, several authors reported that they did not observe RES depression following a primary dose of colloid during a secondary dose of different colloid 38. They attributed this to the fact that opsonization of the first material did not necessarily cause RES depression of the second material.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon of reticuloendothelial blockade has been known for years and describes the depressed rate of clearance of a tracer dose of colloid after intravenous injection of a large blockading dose of colloid. This blockade is often quite specific and will only operate when the test material has the same surface characteristics as the blockading agent (19)(20)(21). Moreover in some studies retiGuloendothelial blockade seemed to be dependent on the persistence in the circulation of the original blockading dose of colloid (20,22).…”
Section: Resultsmentioning
confidence: 99%
“…Thorotrast administered either 3.5 hours or immediately before the start of a continuous intravenous infusion of endotoxin failed to enhance appreciably the febrile response, in contrast to its effect when the same quantities of endotoxin were administered as a single intravenous injection. It may be recalled that RES blockade with any agent is rarely complete and is best demonstrated by rapid injection of a large test bolus of particles (41,42). Consequently, administration of a given quantity of colloid as a slow continuous intravenous infusion would not be expected to impose the same stress on a blockaded RES as would sudden injection of the entire bolus.…”
Section: Discussionmentioning
confidence: 99%